THE ADVOCACY AND COMMUNICATION OF SMOKE-FREE AREA REGULATION IN EAST JAVA, INDONESIA - Sri Widati; Santi Martini; Kurnia Dwi Artanti; Hario Megatsari; Nicola Wiseman; Neil Harris (Indonesian Journal of Health Administration, 2022)
Background: The negative impact of tobacco, especially second-hand smokers, requires imperative actions. Introducing tobacco control measures helps protect the public health. Data suggest that there were approximately 44 million daily smokers in Indonesia comprising 49.8 million males and 3.9 million females over ten years of age. East Java Province had the biggest number of smokers in Indonesia. To reduce trends in smoking behavior, we need to advocate local government to release and implement smoke-free regulations. Aims: The study aims to do action research through advocacy and communication for the regulation of smoke-free areas in East Java Province. Methods: The action research involved 12 districts of East Java Province, Indonesia. The method used in this study was Focus Group Discussion (FGD), one-on-one meeting, in-depth interviews, public speaking, press conference, and press release. Results: Intensive advocacy and communication worked successfully. Eight districts of East Java Province implemented local regulations of smoke-free areas. The advocacy and communication of the regulations made it possible to be implemented. Conclusion: Intensive advocacy and communication improve the awareness of executive and legislative government about the importance of smoke-free area regulations. It will be successful if regular meetings, discussions, press conferences, public speaking, and team work are conducted with many stakeholders.